The Role of Transformational Leadership and Compensation on Employee Performance through Career Development in Small and Medium Enterprises in West Java - Nuranggraeni, Dewi; Aruna, Aruna Putri Maharani; Ade Solahudin (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the effect of transformational leadership and compensation on employee performance, with career development as a mediating variable, in the context of Small and Medium Enterprises (SMEs). The concepts used include the theories of transformational leadership, compensation, career development, and employee performance in the perspective of human resource management. The research approach applied is a quantitative approach with a survey method through distributing questionnaires to 100 respondents, and analyzed using multiple linear regression and sobel test. The results showed that transformational leadership and compensation have a positive and significant influence on employee performance, both directly and through career development. However, the indirect effect through career development is not statistically significant. The implications of these results suggest that SMEs need to focus attention on inspirational leadership practices and fair compensation systems as key performance improvement strategies, even though career development systems are not yet fully structured.